Additive friction stir deposition: a deformation processing route to metal additive manufacturing. Issue 2 (1st February 2021) - Yu, Hang Z.; Mishra, Rajiv S.
Abstract : As the forging counterpart of fusion-based additive processes, additive friction stir deposition offers a solid-state deformation processing route to metal additive manufacturing, in which every voxel of the feed material undergoes severe plastic deformation at elevated temperatures. In this perspective article, we outline its key advantages, e.g. rendering fully-dense material in the as-printed state with fine, equiaxed microstructures, identify its niche engineering uses, and point out future research needs in process physics and materials innovation. We argue that additive friction stir deposition will evolve into a major additive manufacturing solution for industries that require high load-bearing capacity with minimal post-processing. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: This paper delineates additive friction stir deposition, which offers a solid-state deformation processing route to metal additive manufacturing and renders fully-dense material with fine, equiaxed microstructures in the as-printed state.